Individualno relativno preživetje - Pohar Perme, Maja (Informatica Medica Slovenica, 2007)
In survival analysis we are interested in time from the beginning of an observation until certain event (death, relapse). We assume that the final event is well defined, however, that is not always true in practice. Although the cause of death is often hard or even impossible to obtain, our main interest lies in cause specific survival. In such cases, the standard survivaltechniques can not be used. The cure to the problem is the relative survival analysis, that compares the observed survival to the one expected should the patients follow the population survival rates. This paper describesa recently introduced approach, that compares the observed and population data on an individual level, and the R package relsurv, that provides functions for straightforward use of all the relative survival methods.
Keywords: bolniki; Life Tables; mortaliteta; Mortality; preživetje; Preživetje, analiza; Survival Analysis; Umrljivost; Življenjske tablice